Nursing Praxis on Intercultural Care with War-Affected Refugees - Kim L. Larson; Lucyna Płaszewska-Żywko; Natalia Sira; Jami Leibowitz (Global Qualitative Nursing Research)
The purpose of this study was to describe the nursing praxis of nurses and midwives on intercultural care in Poland with refugees from Ukraine. A qualitative descriptive study was conducted by an international, inter-professional research team, co-led by nurse scientists in the USA and Poland. In-depth interviews were completed in 2023 with 15 Polish nurses and midwives who cared for refugees from Ukraine. Nursing praxis was identified in four themes: Mobilizing resources, Clarifying health services, (In)visibility of trauma, and Discerning cultural nuances. Nurses were at the forefront of professional and volunteer efforts to assist refugees. Nursing praxis focused on building trust and creating a “sense of security” among refugees. There was a systemic lack of trauma-informed care and language access for nurses, hindering intercultural care. The study suggests nurses advocate for institutional support of qualified interpreters on health care teams where language differences persist. Nursing education should include intercultural care for war-affected refugees who are likely to experience long term psychological trauma. Ukrainian leaders could partner with investigators on research and program development for sustainable solutions in refugee communities.